Monitoramento de política pública de segurança: o programa educacional de resistência as drogas e a violência (PROERD) no município de São Borja/RS - Cardozo, Isaac Carmo (2019)
The misuse of drugs has been a real threat to humanity, in this sense the military police are developing actions aimed at reducing the demand and supply of drugs, respectively, ie educational programs aimed at drug prevention and repressive actions. in the fight against drugs, such as the Drug Resistance and Violence Educational Program. This program consists of a preventive public policy, working with schools through classes in which the military police officer interacts with students through 10 meetings, warning of the risks inherent in drug use, as well as the resulting violence. In the municipality of São Borja PROERD has been applied since 2002 with a view to reducing crime and violence through joint action between the school, family and military police who, through their instructors, teach classes to elementary school students (5th and 7th grade, aged 9 to 14 years) in 10 meetings through which they seek to prevent and reduce drug use and its consequent violence in the school community. Thus the present work aimed to evaluate the public policy developed by the Military Brigade of São Borja, through the Educational Program of Drug Resistance and Violence - PROERD, with the schools of the municipality. To this end, a qualitative and quantitative research was carried out using the bibliographic, documental and fieldwork means with questionnaire applied to the students of the 6th, 7th and 8th of the Duque de Caxias Municipal School and the Padre Francisco Garcia State Institute. Both schools were chosen because they are located in regions where homicide rates were high in 2017. As a result, it was found that students who participated in PROERD activities feel safer and confident in facing drug issues. Moreover it was found that from the participation in the program students began to see the military police with another view and began to respect the Military Brigade.